In Vitro Evaluation of Rice and Maize Gluten Meals in the Concentrate Mixture of Ruminants - Mahesh, M.S. (Indian Journal of Animal Nutrition, 2021)
Concentrate mixtures formulated to contain graded levels (25, 50, 75 and 100%) of rice gluten meal (RGM) and maize gluten meal (MGM), isonitrogenously replacing groundnut cake (GNC) were evaluated for chemical composition, protein fractions, in vitro gas production and rumen fermentation characteristics. The concentrate mixtures contained an average of 22.1% crude protein (CP). The range of values obtained for various CNCPS protein fractions (% CP) was: 6.9-8.9, 12.7-24.1, 46.3-55.1, 15.3-17.6, 5.4-11.1 for A, B1, B2, B3 and C, respectively across various treatments. Furthermore, rumen undegradable protein was maximum (P<0.01) at 100% MGM inclusion, whilst it was minimum (P<0.01) with GNC-based control. However, intestinal protein digestibility did not differ across treatments. The gas volume (GV) was highest (P<0.01) in control and lowest (P<0.01) in 100% MGM inclusion. Both in vitro dry matter and organic matter digestibility were greatest (P<0.01) at 100% MGM and lowest (P<0.01) at 100% RGM level. Methane, expressed as ml/g was maximum (P<0.01) in control and minimum (P<0.01) at 100% MGM inclusion. In addition, partitioning factor, microbial biomass production (MBP) and MBP: GV were maximum (P<0.01) for 100% MGM and minimum (P<0.01) for the control group. While pH of rumen fluid did not vary, ammonia nitrogen and total volatile fatty acids were found maximum (P<0.01) in control and minimum (P<0.01) at 100% MGM. Moreover, the molar percentage of acetic acid was highest (P<0.01) at 100% MGM but lowest (P<0.01) with 100% RGM diet, whereas the opposite results were true for propionate and butyric acid. These preliminary results suggested 50-75% substitution of GNC by RGM and a similar level of MGM in the concentrate mixture for feeding ruminant animals.